2022
DOI: 10.1136/neurintsurg-2021-018426
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review of intrasaccular flow diverters

Abstract: Treatment of wide-necked complex intracranial aneurysms continues to challenge neurointerventionalists. Intrasaccular flow diverters have expanded the armamentarium considerably and are now used extensively. While five types of devices have already obtained the CE mark for use within Europe, only the Woven EndoBridge (WEB) device is approved by the US Food and Drug Administration. Other intrasaccular devices are the Luna/Artisse Aneurysm Embolization System (Medtronic), the Medina Embolic Device (Medtronic), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…These features lead to aneurysm occlusion after FDD placement due to modification of intra­aneurysmal hemodynamics and neointimal endothelialization [ 2 ]. However, these characteristics also pose considerable drawbacks in particular the strict requirements for dual antiplatelet therapy and the risk of ischemic complications after FDD placement [ 3 ]. According to several large studies on flow diverters, the incidence of ischemic stroke varies from 4.7 to 10% [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These features lead to aneurysm occlusion after FDD placement due to modification of intra­aneurysmal hemodynamics and neointimal endothelialization [ 2 ]. However, these characteristics also pose considerable drawbacks in particular the strict requirements for dual antiplatelet therapy and the risk of ischemic complications after FDD placement [ 3 ]. According to several large studies on flow diverters, the incidence of ischemic stroke varies from 4.7 to 10% [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Neqstent device is a derivative of the CNS. After positioning at the neck of an aneurysm, the coiling microcatheter crosses the mesh into the aneurysm ( 61 , 62 ). The Neqstent device stays within the aneurysm neck and maintains the coils within the aneurysm ( 85 ).…”
Section: New Devicesmentioning
confidence: 99%
“…Luna named Artisse in the newest version ( 5 , 62 ). Previous studies showed that the Luna/Artisse embolization system was safe and effective ( 86 , 87 ).…”
Section: New Devicesmentioning
confidence: 99%
“…nruptured intracranial aneurysms are rather common lesions that are now being diagnosed early as a result of the expansion of noninvasive intracranial vascular imaging techniques. [1][2][3][4][5] With the advent of flow diversion therapy during the past few decades, the goal of endovascular aneurysm treatments has changed conceptually from parent vessel sacrifice or coil packing of the aneurysm fundus to endoluminal restoration of the parent vessel using flow diverters. 1,[5][6][7] The endoluminal devices used for this purpose change the nature of fluid exchange between the aneurysm and parent artery, which consequently facilitates aneurysmal sac thrombosis.…”
mentioning
confidence: 99%
“…[5][6][7] By doing this, they make it possible to repair the parent artery's mural insufficiency, occluding the aneurysm permanently and resolving it over. [1][2][3][4][5]8,9 The 2 Food and Drug Administration-approved flow diverters, pipeline embolization device (PED) and flow redirection endoluminal device (FRED), have demonstrated excellent results in treating unruptured aneurysms in numerous studies conducted internationally, enabling minimally invasive therapy of intracranial aneurysms. [2][3][4][7][8][9][10][11][12][13] The potential for these devices to target and treat aneurysms of diverse sizes, shapes, and even different cerebral sites that have not yet been thoroughly submitted to prospective investigation is quite promising.…”
mentioning
confidence: 99%